MODEL APLIKASI ACCOUNTING DAN FINANCE PADA PT. SHOETOWN KASOKANDEL INDONESIA - Sufajar Butsianto; Mamat Casmat (Teknik Informatika, Universitas Pelita Bangsa, 2019)
This research aims to study and implement the application of accounting standards of PT. Shoetown Kasokandel Indonesia and the implementation of a partial accounting information system on the quality of PT. Shoetown Kasokandel Indonesia. This type of research is quantitative descriptive research. And design for the application of financial accounting information systems of PT. Shoetown Kasokandel Indonesia uses the Application Development (RAD) method. The final result obtained is the analysis and design of an accounting information system that can produce financial reports in the form of general journals, ledgers, collections, and income statements. Keywords : accounting standards, accounting information systems, financial statement quality.